2002
DOI: 10.1258/0023677021912352
|View full text |Cite
|
Sign up to set email alerts
|

PCR for the detection of Streptobacillus moniliformis

Abstract: SummaryStre pto b a c illus m o nil ifo rm is is a Gram-negat ive bac terium found in various laboratory anim al species and is the cause of rat bit e fever and Haverhill fever in man. In order to evaluate a polymerase chain reaction (PCR ) for the detection of this zoonotic bact erium in anim al tissues a set of primers was designed based on the DNA base sequence of part of the 16S rRNA gene from 11 S. m o nili fo rm is strains. T he PCR detected as few as 2±6 copies of S. m o nilifo rm is DNA. A 296 bp DNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 15 publications
2
37
1
Order By: Relevance
“…3-5 8 9 Recently, molecular methods have been used to identify S moniliformis directly in human samples, 6 8 in addition to cultures 5 and organ biopsies of experimentally infected mice and rats. 2 Although S moniliformis could not be isolated here in well individualised colonies by culture from pet specimens, its presence was strongly suggested both by the Gram colouration of cultures and molecular biology data (PCR restriction fragment length polymorphism) on DNA extracts from the cultures and rat biopsy. To our knowledge, the detection of S moniliformis by molecular methods in the pet of a human suffering from RBF has not been reported previously.…”
Section: It Has Beenmentioning
confidence: 80%
See 1 more Smart Citation
“…3-5 8 9 Recently, molecular methods have been used to identify S moniliformis directly in human samples, 6 8 in addition to cultures 5 and organ biopsies of experimentally infected mice and rats. 2 Although S moniliformis could not be isolated here in well individualised colonies by culture from pet specimens, its presence was strongly suggested both by the Gram colouration of cultures and molecular biology data (PCR restriction fragment length polymorphism) on DNA extracts from the cultures and rat biopsy. To our knowledge, the detection of S moniliformis by molecular methods in the pet of a human suffering from RBF has not been reported previously.…”
Section: It Has Beenmentioning
confidence: 80%
“…The 296 bp DNA fragment was amplified and restricted using BfaI, as described previously. 2 This yielded supernumerary fragments but a S moniliformis signature (128, 92, and 76 bp fragments) was detected in the culture and biopsy DNA when compared with the isolated strain (fig 2).…”
mentioning
confidence: 96%
“…Although these assays are sufficiently sensitive, the increasing demand for rapid, more-sensitive tests likely has detracted from their utility. Molecular methods such as PCR show promise and have been used successfully with humans and laboratory animals (4,7,11,43,85). A PCR assay specific for S. moniliformis has been described by Boot et al (11); it uses primers designed on the basis of 16S rRNA gene base sequence data of human and rodent strains of S. moniliformis (forward primer, 5Ј GCT TAA CAC ATG CAA ATC TAT 3Ј; reverse primer, 5Ј AGT AAG GGC CGT ATC TCA 3Ј).…”
Section: Other Methodsmentioning
confidence: 99%
“…The PCR assay generated a 296-bp product which, when discriminated by BfaI restriction enzyme treatment, generated three fragments (128, 92, and 76 bp) specific to S. moniliformis. This assay has been used by others to examine both human-and animal-derived specimens and has been found to distinguish S. moniliformis from other organisms with great accuracy (4,11,85). However, until such an assay becomes more readily available, a diagnosis of S. moniliformis-associated rat bite fever requires a high clinical index of suspicion coupled with the appropriate use of culture and attention to ruling out alternate diagnoses.…”
Section: Other Methodsmentioning
confidence: 99%
“…10,12,97,[102][103][104] The method by Boot et al 102 amplified a 296 bp fragment and showed considerable sensitivity but also some flaws in specificity due to amplicon sequence similarities with Leptotrichia sp., Fusobacterium necrogenes and Sebaldella termitidis. 102,103 Although these non-specificities could be solved by macro restriction with the endonuclease BfaI, Kimura et al 10 advanced this PCR with respect to specificity by improving oligonucleotide primers according to Table 3.…”
Section: Species Specific Pcr For S Moniliformismentioning
confidence: 99%